Dampak Penggunaan Sistem Pembelajaran Blended Learning Bagi Siswa Pada Mata Pembelajaran Ilmu Pengetahuan Sosial di SMP Negeri 18 Kota Bengkulu - Puspita Sari, Oly; Febriani, Deni; Sepri Yunarman, Sepri (JPT : Jurnal Pendidikan Tematik, 2025)
This study aims to determine the impact of using a blended learning system on students in social studies at SMP Negeri 18, Bengkulu City. This type of research is qualitative, a process, and the data collected is presented in the form of qualitative information. Using analytical techniques, the author processed the results of interviews and observations by describing them, then analyzing and concluding them. The data obtained was then selected and compiled. Afterward, the data was classified and analyzed. The results of the study examined the process of implementing a blended learning system in seventh-grade social studies. Blended learning can improve student learning engagement during the learning process. During smooth learning activities, WhatsApp is frequently used, as the learning system during the pandemic is online. Teachers implement different and varied learning strategies, such as sending videos with questions or images to guess the answers. To ensure optimal learning and avoid monotony, teachers deliver learning materials through practice/experimental testing. The impact of using a blended learning system includes: children frequently playing with their phones during online learning, lack of support from both parents and teachers, suboptimal evaluation of the learning system, and lack of parental supervision of cell phone misuse.